”Alice in Nightmareland” – American McGee’s Alice and Alice Madness Returns Games as Gloomy Interpretations of Lewis Carroll’s Works - Chojnacki, Marcin M. (Porównania, 2016)
The author of this paper analyses two video games created by American J. McGee and which are an interesting example of borrowing adaptation accomplished within digital interactive medium. Article also considers the issues of intersemiotic translation in an unstable narrative text, authorship strategy realized by original interpretation of the source material and using themes, characters, events, and places from the original in navigational virtual space. Author points out the multiplicity of possible readings of these titles content while paying attention to the maturity of the medium of video games and their adaptive potential.